Same-Day Regimen as an Alternative to Split Preparation for Colonoscopy: A Systematic Review with Meta-Analysis - Cristina Bucci; Fabiana Zingone; Pietro Schettino; Clelia Marmo; Riccardo Marmo (Gastroenterology Research and Practice)
Background. Split bowel preparation is the best regimen for colonoscopy. However, the same-day regimen can represent a valid alternative, but its use is limited by concerns about its cleansing ability, and to date, no convincing data support its use for routine colonoscopies. Aim. To evaluate the cleansing, compliance, and adverse event rates of the same-day compared to the split regimen. Results. A systematic literature search and meta-analysis was performed. Ten studies were included for a total of 1807 patients (880 in the same-day group and 927 in the split group). Overall, 85.3% patients in the same-day group vs. 86.3% in the split group had an adequate cleansing. Compliance was high for both, although patients were more compliant with the split than with the same-day prep (89.7% for same-day vs. 96.6% for split regimen). Sleep disturbance was more frequent in the split group, while nausea and vomit were more frequent in the same-day group. In the subgroup analysis, polyethylene glycol obtained a better cleansing rate when given as a split dose, with similar compliance and adverse events rates with both regimens. Conclusion. Split and same-day regimens are both useful in bowel cleaning before colonoscopy with a different pattern of adverse events and better compliance for split preparations. Endoscopists can consider the same-day preparation as a valid alternative, especially when the split preparation does not fit the patients’ needs.